Peritonsillar Block as a Treatment for Post-Tonsillectomy Pain in Pediatric Patients with a History of OSA - Merry, Merry; Adi, Made Septyana Parama (Faculty of Medicine, Universitas Padjadjaran, 2025)
Background: Postoperative pain remains one of the most common and distressing complaints following tonsillectomy in children. Among the various strategies explored, regional anesthesia techniques have gained attention for their ability to provide targeted analgesia with minimal systemic side effects. Our objective is to evaluate the effectiveness of ropivacaine and dexamethasone in controlling postoperative pain in children undergoing tonsillectomy, with a focus on its potential to improve recovery outcomes and patient satisfaction.Case: This case involved an 8-year-old male patient who exhibited classic symptoms of OSA, who underwent tonsillectomy procedure. In the anesthetic management, the patient received premedication with midazolam, ondansetron, and intravenous paracetamol. Induction was achieved using propofol, fentanyl, and atracurium, while anesthesia maintenance was provided with Sevoflurane. Prior to extubation, bilateral injections of ropivacaine and dexamethasone were administered in the peritonsillar fossae. Postoperative pain assessments indicated mild pain, with no occurrence of nausea or vomiting. The patient was discharged one day after surgery with manageable pain.Discussion: This case highlights the potential benefit of pre-extubation peritonsillar infiltration with 0.2% ropivacaine (3 mL) and dexamethasone for postoperative pain control. This multimodal, opioid-sparing approach may reduce central sensitization, minimize opioid-related adverse effects, and improve postoperative recovery. Although recent evidence suggests ropivacaine provides superior analgesia at 24 hours compared with bupivacaine, variability in pain timing underscores the need for further research on optimal administration strategies.Conclusion: This case highlights the effectiveness of ropivacaine and dexamethasone in controlling postoperative pain in children.